"I Don't Know, But I'm Trying to Find Out, Okay?": Carlos as Scientist in Welcome to Night Vale. Issue 3 (1st December 2021) - Koopman, Kristen
Abstract : In the audio drama Welcome to Night Vale (2012–) and its spinoff novel It Devours! (2017), the character of Carlos the Scientist functions as a figure for both the larger enterprise of technoscience and a critique of Western technoscience. By pitting the narratives of the mad scientist and the heroic scientist against each other in a single person, Carlos's character development arc shows that both cultural figures rely on the White masculinist tropes and values embedded in Western technoscience. Ultimately, Carlos's arc depicts the limits of these structures and provides a solution in line with feminist epistemologies, emphasizing situatedness over universalism and communitarianism over individualism.